Effect of myasthenia gravis on the surgical outcomes of patients with thymoma. (October 2022) - Miura, Kenji; Doi, Takefumi; Tanaka, Yugo; Hokka, Daisuke; Jimbo, Naoe; Itoh, Tomoo; Maniwa, Yoshimasa
Background: Myasthenia gravis (MG) is the most common paraneoplastic syndrome in thymoma. However, the association between MG and postoperative outcomes is controversial. Therefore, we examined the effect of MG on the surgical outcomes of patients with thymoma. Methods: This study enrolled 145 consecutive patients with thymoma who underwent surgical resection at our institution between January 2000 and December 2020. The patients were classified into thymoma with MG (MG group) and without MG (non-MG group). Data about characteristics of patients, surgical outcomes, and prognostic factors were compared between the two groups. Results: Of 145 patients, 47 (32%) presented with MG and 98 (68%) did not. There was no significant difference in terms of the incidence of postoperative complications, overall survival (OS), and recurrence-free survival (RFS) between the two groups. The deaths were not caused by thymoma. Among the patients aged >60 years, the MG group had a lower survival rate than the non-MG group. In the univariate analysis, age ≥60 years was a poor prognostic factor for OS, whereas in the multivariate analysis, Masaoka stage III and IV classifications were poor prognostic factors for RFS. Conclusion: The incidence of postoperative complications did not differ between patients with thymoma and without MG. In the MG group, age ≥60 years was a poor prognostic factor for OS. The postoperative follow-up of patients aged ≥60 years with thymoma with MG should focus on not only recurrence but also progression of diseases other than thymoma.